Low-temperature atomic layer deposited electron transport layers for co-evaporated perovskite solar cells - Erdenebileg, Enkhtur (2022)
In this work, we explore the potentials and the characteristics of electron-transporting layers (ETL) grown by atomic layer deposition (ALD) at low temperature in co-evaporated perovskite solar cells (PSCs). The thermal-based ALD process has been investigated by tuning the main growing conditions as the number of cycles and the growth temperature. We show that un-annealed ALD-SnO2 thin films grown at temperatures between 80 °C and 100 °C are efficient ETL in n.i.p co-evaporated MAPbI3 PSCs which can achieve power conversion efficiencies (PCEs) consistently above 18%. Moreover, the champion PSC achieved a PCE of 19.30% at 120 °C with 150 cycles. We show that the low-temperature processed ALD SnO2 is very promising for flexible, large-area PSCs and mini-modules. We also report the first co-evaporated PSCs employing low temperature processed ALD ZnO with PCEs approaching 18%. This work demonstrates the potential of the low-temperature ALD deposition method as a potential route to fabricate efficient PSCs at low temperatures.